A Smartphone-Based Virtual Reality Plotting System for STEM Education. Issue 1 (2nd January 2023) - Smith, Joseph R.; Snapp, Bart; Madar, Savva; Brown, Jonathan R.; Fowler, Jim; Andersen, Maeve; Porter, Christopher D.; Orban, Chris
Abstract : We present a free student-facing tool for creating 3D plots and smartphone-based virtual reality (VR) visualizations for STEM courses. Visualizations are created through an in-browser interface using simple plotting commands. Then QR codes are generated, which can be interpreted with a free smartphone app, requiring only an inexpensive Google Cardboard compatible viewer. Example uses for math, physics, chemistry, and other STEM fields are presented, including a project-based assignment for calculus courses at The Ohio State University. The platform enables students, educators, and researchers to create stereoscopic VR visualizations on multiple platforms without needing to learn a complete VR development system.